Uji Aktivitas Penyembuh Luka Bakar dari Gel Getah Jarak Pagar (Jatropha curcas L.) - Meri Sayuti (Herbal Medicine Journal, 2018)
This study uses jatropha resin to treat burns in mice as experimental animals. The researcher conducted a direct experiment to test animals for healing burns from jatropha sap in the form of gel preparations, this can be known from the content of compounds found in jatropha sap that are effective in healing burns. Giving jatropha gel 5%, 10% and 15% (Jatropha curcas Linn.) And giving bioplacenton® 15% gel to the skin of mice (Mus musculus). In this study 25 mice were divided into five groups, namely the group giving bioplacenton® gel (positive control), giving gel base (negative control) and giving jatropha gum gel with various concentrations. The parameters measured in the study were the duration of healing second-degree burns on a daily basis which was marked by a wound that did not appear to be healed (length and width of the wound = 0 cm). The old data on wound healing were analyzed using variance analysis (ANOVA) and continued with the LSD test. It can be concluded that 10% jatropha gum ointment has the potential to accelerate the healing of second degree burns on the skin of mice.